Genetic improvement of robusta coffee (Coffea canephora) in the 20th and 21st centuries: prospects for increasing future breeding effectiveness and impact - Kawuki, Robert; Akpertey, Abraham; Barrera, Santos; Berny Mier y Teran, Jorge C.; Devasia, Jeena; Kraft, Kraig; Akbar, Miftahur Rizqi; Shivalingu, B.R.; Sseremba, Godfrey; Teixeira, Alexsandro; Rocha, Rodrigo Barros; Ha, Phan Viet; et al. (Frontiers in Plant Science, 2026)
Robusta coffee (Coffea canephora), with annual global production ranging from 70 to 76 million bags, has a long history of breeding and crop improvement worldwide. However, breeding efforts to address issues such as subpar farmer profitability and low production per robusta tree still rely on time-consuming approaches that have not changed in decades, making it difficult to respond to evolving needs and market demands. Operationally, the most urgent challenges in robusta breeding are the >20-year variety development time, the limited amount of germplasm with elite traits and heritable genetic variation, and the lack of transdisciplinary collaboration. In this review, we lay the groundwork to address these challenges. We examine pioneering robusta breeding programs in Africa (Uganda, Ivory Coast, Cameroon and Ghana), Asia (Indonesia, India, and Vietnam), and Latin America (Brazil), focusing on trait priorities, the breeding methods employed, the types of varieties developed and disseminated, and the genetic knowledge generated, as well as notable missteps and lessons learned. We then highlight and discuss opportunities for improving robusta breeding efficiency and impact with a specific focus on i) the use of clear target product profiles as guidelines for operationalizing demand-led robusta breeding; and ii) strategies to drive and deploy genetic gains in farmer field. Further we highlight entry points that maximize the impact of integrating modern breeding tools (such as genomics-assisted selection and instrument-based phenotyping) to enhance breeding operations. Our view is based on the understanding that effective breeding integrates processes, products, and human skill at a reasonable cost and within a reasonable timeframe to overcome current and anticipated challenges, particularly those brought on by climate change. Finally, we advocate for multilateral collaborations among industry, academia, and governments, as a powerful approach to bolster the development of the much-needed innovations for farmers. We hope that this retrospective review, from which we derive interventions, will improve the effectiveness and impact of robusta breeding at scale.